The Perspective of the Medan City BPBD in Understanding the Concept of Disaster - Sahara, Lisna; Selasih, Dian; Ginting, Haikal Primsa; Karo-karo, Andrew Winpray; Efendi, Riyan Syah; Harahap, Dinda Salsabila; Putri, Neysa Aulia; Adinda, Salwa Rizky; Siregar, Hairani; B, Berlianti (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to understand the perspective of the Regional Disaster Management Agency (BPBD) of Medan City in interpreting the concept of disaster, as well as how this understanding influences the implementation of duties and cross-agency coordination. The research method used is a descriptive qualitative approach through in-depth interviews with BPBD Medan City officials and documentation studies of relevant policies and legislation. The results of the study indicate that BPBD Medan City possesses a conceptual understanding consistent with Law Number 24 of 2007 on Disaster Management; however, there remains a gap in understanding at the community level. BPBD serves as the main command, coordinator, and executor of disaster management efforts and forms integrated teams according to the type of disaster occurring. Nevertheless, the low level of community literacy regarding the meaning of disasters often leads to misconceptions about BPBD’s responsibilities.